CD44 Is Protective during Hyperoxia-Induced Lung Injury - Windt, Gerritje J. W. van der; Schouten, Marcel; Zeerleder, Sacha; Florquin, Sandrine; Poll, Tom van der (American journal of respiratory cell and molecular biology, 2011)
Patients with acute lung injury or respiratory distress syndrome often require supplemental oxygen to maintain tissue oxygenation; however, this treatment can cause or worsen lung inflammation. CD44 is a transmembrane adhesion molecule that is present on a wide variety of cell types, including leukocytes and parenchymal cells, and is an important player in leukocyte trafficking. The aim of this study was to determine the role of CD44 during hyperoxia-induced (> 95% oxygen) acute lung injury. Whereas all wild-type mice survived the 72-hour observation period, 37.5% of CD44 knockout (KO) mice died. CD44 deficiency was associated with a profound influx of neutrophils into the bronchoalveolar space, in the presence of similar or even lower neutrophil numbers in lung parenchyma, suggesting that CD44 is important for containing neutrophils in the pulmonary interstitium during hyperoxia. In addition, CD44 deficiency resulted in increased IL-6 and keratinocyte-derived chemokine release into bronchoalveolar lavage fluid (BALF). CD44 KO mice further displayed evidence for increased vascular leak and injury of type II respiratory epithelial cells. CD44 protected against bronchial epithelial cell death, as shown by increased epithelial cell necrosis and a trend toward increased BALF nucleosome levels in CD44 KO mice. CD44 can bind and internalize hyaluronic acid (HA), which acts proinflammatory. Concentrations of HA increased in BALF from CD44 KO but not wild-type mice during hyperoxia. These data suggest that CD44 protects against hyperoxia-induced lung injury and mortality by a mechanism that at least in part relies on its ability to clear HA from the bronchoalveolar space.